Two-Dimensional VSi2X2N2 (X = P, As, Sb, Bi) Janus Monolayers: Spin-Polarized Electronic Structure and Perpendicular Magnetic Anisotropy - Zhenxian Zhao; Xiaocha Wang; Wenbo Mi (Crystals, 2023)
The discovery of ferromagnetic two-dimensional (2D) materials provides reference value for the exploration of low-dimensional magnetism and new spintronic devices. The VSi2N4 monolayer is ferromagnetic with half-metallic characteristics, which is a new 2D material in the field of spintronics. Here, the electronic structure and magnetic anisotropy of two-dimensional VSi2X2N2 (X = P, As, Sb, Bi) Janus monolayers are studied systematically via first-principles calculations. The results show that VSi2P2N2, VSi2As2N2 and VSi2Bi2N2 are magnetic, but VSi2Sb2N2 is nonmagnetic. At X = P, As and Bi, VSi2X2N2 Janus monolayers are metallic and ferromagnetic. VSi2P2N2 and VSi2As2N2 show the in-plane magnetic anisotropy, while VSi2Bi2N2 shows the perpendicular magnetic anisotropy (PMA). As the tensile strain increases, the spin-down energy band of the VSi2P2N2 monolayer gradually moves up and the spin-up channel moves down. At ε = +12%, the spin-down band shifts above the Fermi level, showing the half-metallic characteristic with a band gap of 0.775 eV calculated using the Perdew–Burke–Ernzerhof (PBE) exchange–correlation function. The magnetic moment of VSi2Sb2N2 is induced at an electric field of −0.4 V/Å and +0.2 V/Å, where PMA appears. These data provide basic theoretical guidance for the development of low-dimensional spintronic devices.